2010
DOI: 10.3354/dao02187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of urate nephrolithiasis in bottlenose dolphins Tursiops truncatus

Abstract: Few cases of nephrolithiasis (renal calculi) have been reported in bottlenose dolphinsTursiops truncatus. A case-control study was conducted to compare ultrasonographic images and clinicopathologic serum and urine values among 14 dolphins with nephrolithiasis (mild cases: 1 to 19 nephroliths, n = 8; advanced cases: ≥20 nephroliths, n = 6) to 6 controls over an 18 mo period. Archived nephroliths collected postmortem from 7 additional bottlenose dolphins were characterized using quantitative analysis. All advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Our study demonstrated an increase in urinary uric acid, though not after correcting for creatinine, when comparing fresh and frozen-thawed samples. Interestingly, our study population has a high prevalence of ammonium acid urate nephrolithiasis (Venn-Watson et al, 2010a). Follow-up research is needed to assess the need for diluting frozen urine samples for accurate uric acid levels.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our study demonstrated an increase in urinary uric acid, though not after correcting for creatinine, when comparing fresh and frozen-thawed samples. Interestingly, our study population has a high prevalence of ammonium acid urate nephrolithiasis (Venn-Watson et al, 2010a). Follow-up research is needed to assess the need for diluting frozen urine samples for accurate uric acid levels.…”
Section: Discussionmentioning
confidence: 97%
“…Marine mammal urine samples are used to assess renal health, characterize osmoregulation, determine reproductive cycles, assess potential effects of ecosystem contaminants, and detect marine (Ortiz, 2001;Gulland et al, 2002;Roebeck et al, 2005;Venn-Watson et al, 2010a, 2010b. This study focused on the use of comprehensive urinalyses to study individual animal and population renal health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veterinarians can now also consider stem cell therapy when evaluating the treatment options for common dolphin diseases such as corneal trauma and liver disease, both of which have shown promising therapeutic benefits with stem cell treatment in humans [31,32]. Several dolphin diseases have similar human counterparts, including type 2 diabetes [8], urate nephrolithiasis with renal failure [33], and iron overload with liver disease [9,34]. The dolphin may serve as a human model for several disease processes, as was recently proposed for type 2 diabetes [10] and aging studies [35], where new treatment modalities using stem cells could be realized.…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium urate (NH 4 U) nephrolithiasis associated with morbidity has been reported in managed bottlenose dolphins ( Tursiops truncatus ), but research efforts evaluating the pathophysiological and physicochemical mechanisms of nephrolithiasis in dolphins have been limited 1, 2 .…”
Section: Introductionmentioning
confidence: 99%